2017
DOI: 10.1161/circresaha.116.310456
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Temporal Profiling of Transcriptome and Open Chromatin of Early Cardiomyocyte Differentiation Derived From hiPSCs and hESCs

Abstract: Rationale Recent advances have improved our ability to generate cardiomyocytes from human induced pluripotent stem cells (hiPSCs) and human embryonic stem cells (hESCs). However, our understanding of the transcriptional regulatory networks underlying early stages (i.e. from mesoderm to cardiac mesoderm) of cardiomyocyte differentiation remains limited. Objective To characterize transcriptome and chromatin accessibility during early cardiomyocyte differentiation from hiPSCs and hESCs. Methods and Results We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 74 publications
5
106
0
Order By: Relevance
“…Stage-specific peaks are enriched in motifs corresponding to developmental transcription factors ( fig. S6E), in agreement with another recent study (20). Interrogating the regions that transition from B to A, we find that these regions are enriched for peaks present in CP and CM stages and significantly depleted in constitutive peaks (Fig.…”
Section: Main Textsupporting
confidence: 93%
“…Stage-specific peaks are enriched in motifs corresponding to developmental transcription factors ( fig. S6E), in agreement with another recent study (20). Interrogating the regions that transition from B to A, we find that these regions are enriched for peaks present in CP and CM stages and significantly depleted in constitutive peaks (Fig.…”
Section: Main Textsupporting
confidence: 93%
“…However, the majority of studies focused on differentially expressed genes and ignored the high relationship between genes. At present, WGCNA plays a significant role in multiple fields, such as cancer, nervous system and genetic data analysis, which is extremely useful for identifying potential candidate biomarkers or novel treatment targets …”
Section: Introductionmentioning
confidence: 99%
“…At present, WGCNA plays a significant role in multiple fields, such as cancer, nervous system and genetic data analysis, which is extremely useful for identifying potential candidate biomarkers or novel treatment targets. [17][18][19][20] Our study utilized the data related to breast cancer from The Cancer Genomes Atlas (TCGA) database to identify novel lncRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…However, compared to the fraction of high input ATAC-seq peaks (Q. Liu et al, 2017) identified by single cell ATAC-seq (Buenrostro et al, 2015b), single cell uliCUT&RUN libraries identified "gold standard" TF binding sites at a higher rate on average ( Figure S3), demonstrating uncommonly high sensitivity of single cell profiling using the uliCUT&RUN method. For both methods, the incomplete identification of high cell number peaks likely reflects both the technical challenge of recovering every fragment of DNA released from a single nucleus and meaningful biological variation.…”
Section: Single Cell Tf Profiling Using Ulicutandrunmentioning
confidence: 99%